2014
DOI: 10.3171/2014.5.focus1495
|View full text |Cite
|
Sign up to set email alerts
|

Cement augmentation in vertebral burst fractures

Abstract: As a result of axial compression, traumatic vertebral burst fractures disrupt the anterior column, leading to segmental instability and cord compression. In situations with diminished anterior column support, pedicle screw fixation alone may lead to delayed kyphosis, nonunion, and hardware failure. Vertebroplasty and kyphoplasty (balloon-assisted vertebroplasty) have been used in an effort to provide anterior column support in traumatic burst fractures. Cited advantages are providing immediate stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 63 publications
0
44
2
Order By: Relevance
“…While other studies found a higher complication and leakage rate in the augmentation of burst fractures [34], in our study population A1.2 fractures (wegde-impaction) showed a higher leakage rate compared to other fracture forms. The cause for this may be iatrogenically higher PMMA insertion pressures in an attempt to achieve endplate-to-endplate filling in this fracture type, in which one endplate is still intact.…”
Section: Discussioncontrasting
confidence: 48%
“…While other studies found a higher complication and leakage rate in the augmentation of burst fractures [34], in our study population A1.2 fractures (wegde-impaction) showed a higher leakage rate compared to other fracture forms. The cause for this may be iatrogenically higher PMMA insertion pressures in an attempt to achieve endplate-to-endplate filling in this fracture type, in which one endplate is still intact.…”
Section: Discussioncontrasting
confidence: 48%
“…It is unknown whether the augmentation would affect the healing process or whether cyclic loading during rehabilitation would cause the augmentation to become dislodged and migrate [29]. Augmentation of screws in the osteoporotic bone with polymethyl methacrylate (PMMA) is commonly used in fractures of the spine [30, 31] and has been reported in calcaneal fractures [32]. There are no reports on the use of PMMA-augmented screws in osteoporotic ankle fractures.…”
Section: Augmentationmentioning
confidence: 99%
“…By reexpanding the vertebra with balloon tamps, KP reduces the pathologic kyphosis in 60% of patients, improving the restoration of normal vertebral biomechanics, early mobilization, and pain relief in 90% of cases. [19][20][21] Compared with VP, BKP offers superior pain relief at the short-term follow-up with a significant reduction of the visual analog scale (VAS) of pain and improvement of the Oswestry Disability Index (ODI) score. [19][20][21][22][23] Complications Cement venous leakages and new VCFs at distant or adjacent levels are the more frequent complications of this approach.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Compared with VP, BKP offers superior pain relief at the short-term follow-up with a significant reduction of the visual analog scale (VAS) of pain and improvement of the Oswestry Disability Index (ODI) score. [19][20][21][22][23] Complications Cement venous leakages and new VCFs at distant or adjacent levels are the more frequent complications of this approach. Compared with VP, BKP has an inferior rate of cement leakage thanks to the cavity created by the balloon system tamp; cement is injected in low-pressure conditions with a significant reduction of the risk of cement leak.…”
Section: Resultsmentioning
confidence: 99%